2015
DOI: 10.2217/pgs.15.85
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Role of Admixture in Cancer Therapy Via in Vitro Drug Response and Multivariate Genome-Wide Associations

Abstract: Aim:We investigate the role of ethnicity and admixture in drug response across a broad group of chemotherapeutic drugs. Also, we generate hypotheses on the genetic variants driving differential drug response through multivariate genomewide association studies. Methods: Immortalized lymphoblastoid cell lines from 589 individuals (Hispanic or non-Hispanic/Caucasian) were used to investigate doseresponse for 28 chemotherapeutic compounds. Univariate and multivariate statistical models were used to elucidate assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Of course, the response to anti-cancer agents and toxic chemicals is the measurable phenotype that associates with the residual Neanderthal variance in anatomically modern humans, but we hypothesize that Homo sapiens may have evolved resistance to a diverse array of phytochemicals due to a more heterogeneous diet relative to the predominantly meat-based diet of Neanderthals. Previous studies have shown the influence of race and ethnicity on the dose response phenotype ( Shord et al, 2006 ; Sharma, Cogswell & Li, 2008 ; Fu et al, 2014 ; Abdo et al, 2015 ; Jack et al, 2015 ). In this study, we show a strong association between Neanderthal ancestry and the dose response phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of course, the response to anti-cancer agents and toxic chemicals is the measurable phenotype that associates with the residual Neanderthal variance in anatomically modern humans, but we hypothesize that Homo sapiens may have evolved resistance to a diverse array of phytochemicals due to a more heterogeneous diet relative to the predominantly meat-based diet of Neanderthals. Previous studies have shown the influence of race and ethnicity on the dose response phenotype ( Shord et al, 2006 ; Sharma, Cogswell & Li, 2008 ; Fu et al, 2014 ; Abdo et al, 2015 ; Jack et al, 2015 ). In this study, we show a strong association between Neanderthal ancestry and the dose response phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have shown strong differences in drug response in the LCL model for both pharmaceuticals and environmental chemicals. Differences in dose response phenotypes were observed between Hispanic and Caucasian populations for 28 chemotherapy drugs ( Jack et al, 2015 ) and significant variation in EC 10 was observed across the globally diverse populations from the 1000 Genomes Project (1000G) for 179 environmental chemicals ( Abdo et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…iControl software (Version 1.11) was then used to measure the fluorescence intensity of resarufin at EX535nm and EM595nm. The resulting relative fluorescence units are proportional to cellular redox activity, which is a common proxy for the quantity of living cells 56 .…”
Section: Methodsmentioning
confidence: 99%
“…These differences can be explained by genetic variation in ADME-related genes [93]. ADME-related genetic variability often differs across populations [94] and helps to explain the link between ancestry and variable chemotherapy drug response [95]. Li et al observed greater diversity in ADME genes for the African-American population compared with European and African populations [96], predisposing African-Americans to more variable drug response.…”
Section: Genomics and Epigenomics Of Symptoms And Chemotherapy Metabomentioning
confidence: 99%